Medical Equipment Procurement Management Strategy Efficiency-Based (Study on the Intensive Care Unit of Pradipa Medika Hospital in Kuningan Regency) - Wulan Ervinna; Heris Hendriana; Rinawati Rinawati (Research of Service Administration Health and Sains Healthys, 2025)
The development of information technology in the health sector has significantly transformed patient data management systems through the implementation of electronic medical records (EMR). This study aims to analyze the influence of six variables in the PIECES model — performance, information, economy, control, efficiency, and service — on the tangible aspects of healthcare services. This quantitative study employed a survey method involving 230 healthcare professionals using EMR at the Women Empowerment and Child Protection Ministry Clinic (Kemen PPPA). The results reveal that all six PIECES variables simultaneously have a significant effect on tangible aspects of healthcare services. Partially, performance, efficiency, and service variables contribute most dominantly to improving tangible aspects such as service speed, accessibility of patient data, and user-perceived facility comfort. These findings indicate that optimizing EMR implementation based on the PIECES framework can enhance service quality directly perceived by patients.